Evaluation of mechanical properties of concrete manufactured with fly ash, bagasse ash and banana fibre. (2021) - Dhawan, Akshay; Gupta, Nakul; Goyal, Rajesh; Saxena, K.K.
Abstract: Concrete is the most dynamic engineering material in construction industry because of its strength properties as well as its durability. The consumption of raw materials not only depleted natural resources but also increases the toxic material in the environment by the construction industries. The substitute products have been found to save the environment and natural resources up to some extent. In the same context, some usual composition of concrete mix is replaced by industrial/ natural wastes such as Fly Ash, Sugarcane bagasse ash and Banana fibre. The samples were prepared with the different composition using different % replacement of cement and sand. Therefore, concrete mix is developed using fly ash (replacing 20% of cement) and partial replacing sand by an industrial waste i.e. Sugarcane bagasse ash (replacing 0%, 10%, 20% of sand) with adding banana fiber (0%, 2.5%, 5%). Samples were evaluated and compared with standard concrete mix under characteristic compressive strength and flexural strength. It was observed that observed that addition of 2.5% of banana fibre in Cement; partially replaced by 20% of Fly Ash, and Sand; partially replaced by 10% of Bagasse Ash is the best Combination which gives better mechanical properties.